ORGANIZING THE DEVELOPMENT OF MODERN BOARDING SCHOOL EDUCATION - Damiri, Adam; Syaputra, Gunawan (As-Sulthan Journal of Education, 2024)
Modern Islamic boarding school is a concept that aims to combine two important components. Integration of the Islamic boarding school curriculum in the context of the national curriculum in Islamic boarding schools in education, namely the Islamic boarding school curriculum and the national curriculum. In this case, the main aim of curriculum integration is to unite religious education taught in Islamic boarding schools with general education regulated in the national curriculum, so that students can obtain comprehensive knowledge and skills. This research uses a qualitative approach. The main reason researchers used this approach was to explore various data regarding the formation of prophetic leadership through the Islamic boarding school's mandatory work program. This type of research is a case study. It is called a case study because this research seeks to find the system that forms the prophetic leadership spirit of students in Islamic boarding schools through the Islamic boarding school assignment delivery program. Therefore, data collection was carried out in three ways, namely observation, interviews and documentation. The purpose of this writing is to find out about organizing modern Islamic boarding school education, after research into organizing the development of modern Islamic boarding school education requires the structure and principles of organizing in modern Islamic boarding school education. The structure of modern Islamic boarding school education that must exist is: a. Leaders or Teachers of Islamic Boarding Schools. b. Daily Management Board (BPH) for Academic Affairs. c. Dormitory or Islamic boarding school sector. d. Field of Independence and Skills Developmente. e. Health and Counseling Sector. f Extracurricular Sectors and Talent Interest Development. g. Finance and Administration Unit